Karakteristik Penyimpanan Biogas Menggunakan Karbon Aktif Tempurung Kelapa Dengan Variasi Waktu Aktivasi Microwave - Wardi, I Gusti Agung Putu Denny Putra; Astawa, Ketut; Sucipta, Made (Teknik Desain Mekanika, 2025)
Abstract With the increasing global energy demand and awareness of the importance of renewable energy, biogas is becoming one of the attractive alternatives. However, the challenge of biogas storage is a major obstacle to its widespread utilization. Activated carbon especially from coconut shells, has great potential as an adsorbent to overcome this problem. This study aims to optimize the storage capacity of biogas by varying the activation time of 10 minutes, 20 minutes, and 30 minutes on microwave-activated coconut shell-based activated carbon. Biogas utilization results from reducing the amount of biogas storage mass when filling with the remaining amount of biogas storage mass released. The results showed that the activation time of 30 minutes resulted in a higher biogas storage capacity, hence the biogas utilization also increased. This suggests that optimized coconut shell-based activated carbon can be an effective solution for biogas storage. Keywords: Biogas, Activated carbon, Activation time, Biogas storage, Adsorbed Natural Gas (ANG), Microwave.